Provision of spiritual care in the neonatal intensive care unit in Iran in healthcare providers' perspective: a qualitative study - Haydeh Heidari; Nasrin Mehrnoush; Mansoureh Karimollahi (Mashhad University of Medical Sciences, 2022)
Background: The provision of spiritual care along with holistic and comprehensive care is an important need for families with children hospitalized in an intensive care unit. This study aimed to explore the perceptions of healthcare providers regarding the spiritual care of parents with a newborn in a neonatal intensive care unit (NICU) in Iran.Methods: This study was conducted using conventional qualitative content analysis, which adopts open coding, classification, and abstraction. A total of eight nurses and one doctor participated to be interviewed.Results: Based on data analysis, three categories of nursing support needed for spiritual care as well as the necessity of changes in structural conditions were identified in this study.Conclusion: Hospital administrators must undertake measures to change circumstances in NICUs. In addition, nurse managers should plan training courses on the importance of providing spiritual care to patients and their families.